Histology of a novel injectable filler (polymethylmethacrylate and cross-linked dextran in hydroxypropyl methylcellulose) in a rat model. (August 2014) - Lee, Young Bok; Park, Sae Mi; Song, Eun Jong; Park, Jun-Gyu; Cho, Kyoung-Oh; Kim, Jin Wou; Yu, Dong Soo
Abstract A novel injectable filler of polymethylmethacrylate (PMMA) and cross-linked dextran in hydroxypropyl methylcellulose was introduced in the commercial filler market. For soft tissue augmentation, safety and biocompatibility should be evaluated and the stability at the implantation site should be assessed using histologic evaluation. In order to evaluate the biocompatibility of the novel soft tissue filler, PMMA and cross-linked dextran in hydroxypropyl methylcellulose was subdermally injected into the skin of Sprague–Dawley Rats. Histologic evaluation was performed at 13 weeks and 12 months after the injection. Inflammatory cell infiltration, neovascularization, and fibrosis were scored according to defined grading systems. The mean score of the histologic evaluation was 5.7 and 3.9 at 13 weeks and 12 months, respectively. At 12 months after injection, the PMMA and cross-linked dextran in hydroxypropyl methylcellulose appeared to be kept in place through fine fibrous capsules. The mixture of PMMA and cross-linked dextran in hydroxypropyl methylcellulose can be safely applied for soft tissue augmentation with longevity of greater than 12 months.